2020
DOI: 10.1002/fes3.238
|View full text |Cite
|
Sign up to set email alerts
|

Genetic factors increasing barley grain yields under soil waterlogging

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 55 publications
0
35
1
Order By: Relevance
“…For example, in APSIM-Wheat and APSIM-Barley, aeration deficit impacts on crop growth range from maximum sensitivity at emergence to no sensitivity during grain filling, while the crop sensitivity factor in Equation 3 was 0.16 for crop establishment, 0.18 for early vegetative stages, 0.38 for late vegetative stages, 0.21 for flowering, and 0.06 for yield formation. These values contrast with experimental work by Liu, Harrison, Ibrahim, et al (2020), who showed that barley was least sensitive to early waterlogging and most sensitive to waterlogging near anthesis. Instead of arbitrary, crop-specific empirical factors related to waterlogging stress at various phenological stages, we suggest that models be based on crop physiological principles, which could then form the basis for simplified but well-informed phenomenological descriptions of such processes (Meinke et al, 1998).…”
Section: /2020ef001801contrasting
confidence: 98%
See 3 more Smart Citations
“…For example, in APSIM-Wheat and APSIM-Barley, aeration deficit impacts on crop growth range from maximum sensitivity at emergence to no sensitivity during grain filling, while the crop sensitivity factor in Equation 3 was 0.16 for crop establishment, 0.18 for early vegetative stages, 0.38 for late vegetative stages, 0.21 for flowering, and 0.06 for yield formation. These values contrast with experimental work by Liu, Harrison, Ibrahim, et al (2020), who showed that barley was least sensitive to early waterlogging and most sensitive to waterlogging near anthesis. Instead of arbitrary, crop-specific empirical factors related to waterlogging stress at various phenological stages, we suggest that models be based on crop physiological principles, which could then form the basis for simplified but well-informed phenomenological descriptions of such processes (Meinke et al, 1998).…”
Section: /2020ef001801contrasting
confidence: 98%
“…The growth stage i can be planting to terminal spikelet, terminal spikelet to flowering, flowering, grain filling, or maturity. This approach allows variation in the extent of waterlogging according to growth stage, but the model does not account for the delay in phenology caused by waterlogging in greenhouse experiments (Liu, Harrison, Ibrahim, et al, 2020). Li et al (2016) compared both methods in GLAM-WOFOST then revised the runoff, surface storage, and infiltration scheme in GLAM, resulting in an improvement in model validation (data set from wheat production data from 1985 to 2000 of Jiangsu, Anhui, and Zhejiang provinces in China), with RMSE and R 2 values of 307 kg ha −1 and 0.78 in using WSF HU (Hu et al, 2004) and RMSE and R 2 values of 307 kg ha −1 and 0.71 in using WSF HU .…”
Section: Glam-wofostmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a lower population may allow for wider plant spacing, which impacts the leaf area, light interception, and canopy apparent photosynthesis ( Tao et al, 2018 ). This leads to the production of more photosynthetic products that may significantly increase the spike number and kernel number, compensating for detrimental effects of lower population on other yield components to some degree ( Liu et al, 2020 ). Ensuring early and vigorous crop establishment is a key factor in achieving maximum wheat yield under the RW cropping system.…”
Section: Discussionmentioning
confidence: 99%